3DN C/SiC-MoS2 self-lubricating composites with high friction stability and excellent elevated-temperature lubrication. Issue 14 (November 2021) - Yang, Yubo; Zhao, Yu; Mei, Hui; Cheng, Laifei; Zhang, Litong
Abstract: Aerospace lubrication system requires materials with stable service life and excellent elevated-temperature lubrication performance. Herein, MoS2 lubricants were used to fill the pores of three-dimensional needled (3DN) C/SiC to prepare 3DN/SiC-MoS2 self-lubricating composites. The effects of 3DN C/SiC-MoS2 self-lubricating composites under different friction time and temperatures were investigated. Results reveals that the average friction coefficients of 3DN C/SiC-MoS2 self-lubricating sample fluctuated between 0.118 and 0.202 under different friction time, and the wear rate maintained about 10 −4 mm 3 /(N m). Especially, the sample under the long friction time of 7200s, with average friction coefficient of 0.161 and lowest wear rate of 3.57×10 -5 mm 3 /(N m), indicating that the self-lubricating sample has a stable service life. Additionally, the average friction coefficients of 3DN C/SiC-MoS2 self-lubricating sample at 200℃ and 400℃ were lower than that of at 25℃, and the wear rate increased within the order of 10 -4 mm 3 /(N m) as the temperature increased.